IMPLEMENTATION OF THE SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) METHOD TO IMPROVE FOURTH-GRADE STUDENTS' TEXT LITERACY AT MIS HAYATUL ISLAMIYAH CINANGKA - Amalia, Filzah Nur (BAIK Publishers, 2025)
Active participation in class can improve understanding of the material, thus becoming a prerequisite for working with skilled and professional human resources who are experts in their fields and contributing to the quality of the learning process. This study aims to examine the influence of (1) the influence of lecturers' teaching styles on student learning satisfaction (2) the influence of lecturers' teaching styles on student learning motivation (3) the influence of student learning motivation on learning satisfaction (4) the influence of teaching styles directly on learning motivation through learning satisfaction. The population in this study was students in South Tangerang. The research sample was selected using a purposive sampling method of 120. The analytical method used in this study was mediation regression analysis. The results of this study indicate a significant influence of (1) lecturers' teaching styles on student learning satisfaction (2) the influence of lecturers' teaching styles on student learning motivation (3) the influence of student learning motivation on learning satisfaction (4) the influence of teaching styles directly on learning motivation through learning satisfaction